Romania : Fourth Review Under the Stand-By Arrangement and Request for Waivers of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
Romania's macroeconomic performance remains broadly in line with the program, but the recent strengthening of domestic demand and nonobservance of four performance criteria require corrective measures. Discussions on policies for 2003 took place in the context of increasing risks stemming from unfavorable external developments, accelerating domestic demand, and a widening of the current account deficit. IMF staff noted the delay in preparing the privatization strategy for the energy sector, and encouraged the authorities to make every effort to complete the privatization of the energy sector.